Effect of trisodium citrate on the formation and structural, optical and photocatalytic properties of Sr-doped ZnO - Sumetha Suwanboon (2020)
© 2020 Elsevier B.V. Sr-doped ZnO powders were precipitated from a citrate-modified zinc precursor solution. The phase formation, morphology and optical properties of the powders were studied using X-ray diffractometry (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), diffuse reflectance spectroscopy (DRS) and photoluminescence spectrometry, respectively. The photocatalytic degradation of an aqueous methylene blue (MB) solution over the synthesized powders was investigated by UV-vis spectrophotometry. Citrate ions played an important role in controlling the morphology of the synthesized ZnO powders and the formation of the Sr-doped ZnO phase. ZnO powders doped with 0–15 mol% Sr formed completely at the highest mole ratio of trisodium citrate dihydrate to zinc nitrate tetrahydrate (R = 5). At R = 5, when the Sr ion concentration was increased from 0 to 15 mol%, crystallite size of ZnO decreased from 38.63 to 31.61 nm and the optical band gap decreased from 3.157 to 3.129 eV. The photocatalytic degradation of an aqueous MB solution under UV irradiation over the Sr-doped ZnO powders increased as a function of irradiation time and Sr ion concentration in the range of 0–10 mol%. The highest photocatalytic activity over 10 mol% Sr-doped ZnO powder was about 98% and the photocatalytic activity of the powder remained higher than 87% for five cycles of reuse.